CooL-AgentSpeak: Enhancing AgentSpeak-DL Agents with Plan Exchange and Ontology Services - Mascardi, V.; Ancona, D.; Bordini, R. H.; Ricci, A. (2011 IEEE/WIC/ACM International Conferences on Web Intelligence and Intelligent Agent Technology, 2011)
In this paper we present CooL-Agent Speak, an extension of Agent Speak-DL with plan exchange and ontology services. In CooL-Agent Speak, the search for a plan is no longer limited to the agent's local plan library but is carried out in the other agents' libraries too, according to a cooperation strategy, and it is not based solely on unification and on the subsumption relation between concepts, but also on ontology matching. Belief querying and updating take advantage of ontological reasoning and matching as well.